Some are more South African than others? The case of the Twitter hashtag #WeRejectMayorOfJHB - Savious, Tarisayi Kudzayi (Penerbit Universiti Kebangsaan Malaysia, 2022)
There is a growing concern about discriminatory behaviours on social media in recent years. However, there is a dearth of literature focused on the abuse of foreigners on South African Twitter. This paper interrogates the views of the online community on South African Twitter on the appointment of children of immigrants to political office. A case study of the hashtag #WeRejectMayorOfJHB was carried out. The scapegoating theory guided this study. The hashtag started on social media following the election of Jolidee Matongo, mayor of the City of Johannesburg, on the 10th of August 2021. Within the hashtag, the researcher used confirming and disconfirming sampling to sample 30 tweets. The sample of tweets was drawn from a population of 120 tweets on South African Twitter within 24 hours preceding the election of Jolidee Matongo as the new mayor of Johannesburg. Critical discourse analysis was used. The findings revealed that there were multiple dissonances in the construction of South African citizenship in general and Jolidee Matongo’s citizenship. The views on South African citizenship under the hashtag were at odds with the Constitution and the laws of South Africa. Racial and afrophobic perspectives emerged from the analysis.